THERMAL DEFORMATION BEHAVIOR AND FLOW STRESS MODEL OF EH40 STEEL - JIN HeRong; DUAN ChangXin; DAI Chao (Jixie qiangdu)
In order to study the effect of deformation parameters on the flow stress of EH40 steel plate during hot working,using Gleeble-3800 tester to perform thermal compression simulation of specimen,the true stress-strain curve of EH40 shipboard steel under temperature conditions of 0. 1 s-1～ 10 s-1 strain rate and 900℃ ～ 1 200℃ is obtained. By analyzing the curve,we find that deformation temperature and strain rate all have important effects on the dynamic recrystallization and dynamic recovery of EH40 plate steel,increasing the deformation temperature or reducing the strain rate is conducive to the occurrence of dynamic recrystallization during deformation,which contributes to grain refinement of the material. A hyperbolic sine model with ZeneHollomon parameters is adopted,the thermal deformation equation,activation energy of thermal deformation,and mathematical model of Z parameters were obtained. It is verified that the average error between the calculated value and the experimental value of the established constitutive relation is 3. 13%,which can well reflect the actual hot deformation behavior of EH40 ship-board steel.